Milk and bullets - Errington, Sarah; Alwyn, Richard ([S.l.] : Double E [production company] ; Bristol : BBC Education and Training)
Documentary about Karamoja people in Africa. Described how cows be a central to the life of African people. Also includes how Karamoja people life are related to cows and bullets of the gun.
Narrator, Andrew Sachs ; film editor, Michael Flynn ; series editor, Alan Bookbinder
Keywords: Ethnology -- Africa; Cows -- Africa; Africa -- Social life and customs